Biomineralized hybrid nanodots for tumor therapy via NIR-II fluorescence and photothermal imaging - Niu, Xuegang; Wei, Penghui; Sun, Jiangnan; Lin, Yuanxiang; Chen, Xiaoyong; Ding, Chenyu; Zhu, Yang; Kang, Dezhi (Frontiers in Bioengineering and Biotechnology, 2022)
Chemodynamic therapy (CDT) is an emerging and promising therapeutic strategy that suppresses tumor growth by catalytically converting intracellular hydrogen peroxide (H2O2) into highly-reactive hydroxyl radicals (•OH). However, the inherent substrate of H2O2 is relatively insufficient to achieve desirable CDT efficacy. Therefore, searching for integrated therapeutic methods with synergistic therapeutic modality is especially vital to augment therapeutic outcomes. Herein, we reported nanodot- CuxMnySz @BSA@ICG (denoted as CMS@B@I) and bovine serum albumin (BSA)-based biomineralization CuxMnySz (CMS) loaded with photodynamic agent-indocyanine green (ICG). CMS@B@I converts endogenous hydrogen peroxide (H2O2) into highly active hydroxyl radical (OH) via Fenton reaction, and effectively produces reactive oxygen species (ROS) after being exposed to 808 nm laser irradiation, attributable to the excellent photodynamic agent-ICG. This results in eliciting a ROS storm. Additionally, CMS@B@I exhibits a superior photothermal effect under NIR-II 1064 nm laser irradiation to enhance tumor CDT efficacy. The NIR-II fluorescence imaging agent of ICG and the excellent photothermal effect of CMS@B@I are highly beneficial to NIR-II fluorescence and infrared thermal imaging, respectively, resulting in tracing the fate of CMS@B@I. This study attempts to design a bimodal imaging-guided and photothermal-enhanced CDT nanoagent for augmenting tumor catalytic therapy.